3,3′-Diindolylmethane Promotes Gastric Cancer Progression via β-TrCP-Mediated NF-κB Activation in Gastric Cancer-Derived MSCs - Shi, Hui; Sun, Yaoxiang; Ruan, Hongru; Ji, Cheng; Zhang, Jiahui; Wu, Peipei; Li, Linli; Huang, Chihan; Jia, Yuanwang; Zhang, Xu; Xu, Wenrong; Jiang, Jiajia; et al. (Frontiers in Oncology, 2021)
Gastric cancer is a malignant tumor characterized by high morbidity and invasion. Surgery combined with chemo-radiotherapy is the most common treatment for gastric cancer, while multiple drug resistance always results in treatment failure. Once the anti-tumor drugs enter the tumor foci, tumor cells as well as those found in the microenvironment are affected. However, the effects of drugs on tumor microenvironment (TME) are easily overlooked. In this study, we investigated the effects of the anti-cancer drug 3,3’-diindolylmethane (DIM) on gastric cancer-derived mesenchymal stem cells (GC-MSCs) and their subsequent impact on cancer progression. Surprisingly, we found that the therapeutic concentration of DIM upregulated the expression level of tumor-related factors such as CCL-2, IL-6, and IL-8 in GC-MSCs. The conditioned medium of DIM-treated GC-MSCs promoted the proliferation, invasion, and migration of gastric cancer cells in vitro and tumor growth in vivo. Mechanistically, DIM enhanced the expression of β-TrCP, an E3 ubiquitin ligase leading to iκBα degradation and NF-κB activation in GC-MSCs. The β-TrCP knockdown partially eliminated positive results caused by DIM. Our results showed that the therapeutic dosage of DIM induced cell death in cancer cells, while enhancing MSC paracrine functions in the stroma to offset the original DIM effect on cancer cells. These findings provide a new mechanism of anti-cancer drug resistance and remind us to adjust the chemotherapeutic scheme by combining the anti-cancer drug with an appropriate signaling pathway inhibitor to block the side effects of drug on targeted TME cells.